IMPLEMENTASI RETRIBUSI PELAYANAN PASAR SECARA ELEKTRONIK (E-RETRIBUSI) DI KABUPATEN TEMANGGUNG - Aditya Hendi Kurniawan; Muda Setia Hamid (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This study aims to evaluate the implementation of electronic market service fees (E- Retribution) in Temanggung Regency. The research was conducted at the Office of Cooperatives, Small and Medium Enterprises and Trade, Temanggung Regency in December 2022. This type of research is descriptive qualitative. Data collection techniques using interviews, observation and documentation.The data analysis used is Miles and Huberman Interactive Data Analysis Model which consists of data reduction, data presentation and conclusion/verification.The research results show that: The stages in implementing market service fees electronically (E-Retribution) are coordination of parties related to E-Retribution, making E-Retribution applications, making merchant NPWRDs, socializing E-Retribution to market traders, and appointing special officers to carry out assistance and E-Retribution assistance Obstacles faced in implementing E-Retribution are that the internet network is not optimal, there are frequent disruptions to the E-Retribution application system with MPOS, a balance filling system that is not practical, Standard Operational Procedure (SOP) does not yet exist, application dashboard displays and features are not all presented in the E- Retribution application. 3). Efforts in implementing E-Retribution are coordinating with the Office of Communication and Informatics to handle the internet network, coordinating with E-Retribution application vendors and Bank Jateng to overcome disruptions to the E-Retribution system, E-Retribution SOPs are being prepared and discussed internally by the Service and coordination with parties vendor regarding the addition of data search features and adjustments to the appearance of the E-Retribution application dashboard according to needs so that it will be easier to understand.